2018
DOI: 10.4142/jvs.2018.19.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and phylogenetic characteristics of non-O157 Shiga toxin-producingEscherichia coliisolates from retail meats in South Korea

Abstract: Herein, we report the pathogenic and phylogenetic characteristics of seven Shiga toxin (Stx)-producing Escherichia coli (STEC) isolates from 434 retail meats collected in Korea during 2006 to 2012. The experimental analyses revealed that all isolates (i) were identified as non-O157 STEC, including O91:H14 (3 isolates), O121:H10 (2 isolates), O91:H21 (1 isolate), and O18:H20 (1 isolate), (ii) carried diverse Stx subtype genes (stx1, stx2c, stx2e, or stx1 + stx2b) whose expression levels varied strain by strain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…In addition, the sequence types of the two STEC O157 were determined as ST542 (Table 1). Although the sequence type of STEC O157 is normally determined as ST11 [61, 72], O157 isolates determined as non-ST11 have been also documented elsewhere. For instance, four O157 isolates from the US and/or UK are determined as ST1804 [62].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sequence types of the two STEC O157 were determined as ST542 (Table 1). Although the sequence type of STEC O157 is normally determined as ST11 [61, 72], O157 isolates determined as non-ST11 have been also documented elsewhere. For instance, four O157 isolates from the US and/or UK are determined as ST1804 [62].…”
Section: Discussionmentioning
confidence: 99%
“…discovered subtilase cytotoxin (SubAB) as a novel family of AB 5 cytotoxins in the locus of enterocyte effacement (LEE)‐negative Shiga‐toxigenic Escherichia coli (STEC) O113:H21 98NK2 strain. The gene encoding subAB was predominantly detected in LEE‐negative STEC, 2–5 not in LEE‐positive STEC such as the O157:H7 strain. Recent studies indicate that LEE‐negative STEC infections are increasing globally 6–8 …”
Section: Characterization and Activity Of Subabmentioning
confidence: 96%
“…In our attempt to define a pathogenic clone(s) of STEC in Korea, it was demonstrated that the STEC O91:H14 serovar belonged to the ST33 lineage and was highly prevalent among human patients and retail meat samples collected during 2003 to 2014 [8]. Although the isolates do not belong to the big four non-O157 STEC, the same serotypes have been reported among the most common STEC isolates from diarrheal patients without HUS in Germany [11].…”
mentioning
confidence: 99%
“…As shown in Fig. 1, PFGE profiles with > 80% similarity were analyzed as previously described [8]. The results showed that 16 of the 17 STEC O91:H14 isolates were classified mainly into three pulsotypes: the first included six isolates from human patients, which possessed both stx 1 and stx 2dact genes (designated pulsotype A); the second contained five isolates from human patients, which harbored only the stx 2dact gene, except one patient (H2003) who had both stx 1 and stx 2dact genes (pulsotype B); and the third comprised three isolates from human patients that had only the stx 1 gene and two from retail beef samples harboring both stx 1 and stx 2b genes (pulsotype C).…”
mentioning
confidence: 99%
See 1 more Smart Citation